Pengaruh Brand Experience Dan Brand Love Terhadap Customer Engagement Dan Customer Loyalty Pada Pengguna Maskapai Penerbangan Lcc Di Indonesia Yang Dimoderasi Oleh Service Quality - Dramawan, Yosep; Syah, Tantri Yanuar Rahmat (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
Brand love plays an important role in instilling customers' emotional bonds with the brand as a tool for customer engagement to maintain long-term relationships, so that customers will not switch and will continue to make repeated and continuous product purchases (loyal). This study aims to explore the relationship between the variables of brand experience, brand love, customer engagement and customer loyalty on LCC airline users in Indonesia which is moderated by service quality. This research was conducted on LCC airline users in Indonesia using a purposive sampling method as a method to determine the sample. The data in this study were analyzed using SPSS and SEM Lisrel. The results of this study indicate that brand experience has no effect on brand love, then brand love has an effect on customer engagement. Furthermore, customer engagement has a positive influence on customer loyalty. Next, service quality succeeded in moderating the relationship between brand love and customer engagement, but failed to moderate brand experience and brand love. For LCC airlines, the majority of Indonesian consumers are more interested in cheap ticket prices compared to their flying experience when choosing an LCC airline. Therefore, in order to build brand love, LCC airlines are advised to give more consideration to ticket prices, giving promos or discounts for each flight from the LCC airline